Recuperación del suelo y estructura de las comunidades fruticosas tras abandono de cultivos eumediterráneos en el CW Ibérico - Matias M.D.; Garcia J.A.; Puerto A.; Saldaña J.A. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
A study is made of secondary succession following abandonment of cultivation on hillside terraces. The ordering analyses of the shrub species reveal a superposition of bioclimatic effects and those due to the impact of human activity, with a predominance of the later. Successional development is clearly detectable, reaching after 30-40 years of abandonment a well developed forest stage in zones, that due to their inclination, would not have allowed such to occur in natural conditions. The changes undergone by the soil variables analysed and the successional differences depending on the initial type of exploitation are other aspects dealt with.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)